After the pandemic: new responsibilities - Levy, NL; Savulescu, J (Oxford University Press, 2021)
Seasonal influenza kills many hundreds of thousands of people every year. We argue that the current pandemic has lessons we should learn concerning how we should respond to it. Our response to the COVID-19 not only provides us with tools for confronting influenza; it also changes our sense of what is possible. The recognition of how dramatic policy responses to COVID-19 were and how widespread their general acceptance has been allowed us to imagine new and more sweeping responses to influenza. In fact, we not only can grasp how we can reduce its toll; this new knowledge entails new responsibilities to do so. We outline a range of potential interventions to alter social norms and to change structures to reduce influenza transmission, and consider ethical objections to our proposals.